ASPs versus MOTS software solutions - MA, Dan (Institutional Knowledge at Singapore Management University, 2005)
Application Service Providers (ASPs) deliver on-demand information processing services to user firms via the Internet. They have been an attractive alternative to purchasing, installing, and maintaining modifiable off-the-shelf (MOTS) software solutions. We study several critical aspects of a user firm's choice between an ASP and MOTS software. The competitive model considers heterogeneous users who differ in terms of their expected transaction volume, while ASPs and MOTS vendors differ in terms of their pricing structure, setup cost, system customization, and service level arrangement. Our results identify and characterize the equilibrium conditions under which ASPs and MOTS vendors can coexist in a competitive market, and they explain which firms could be the primary beneficiaries of each vendor type. We show that the value added by ASPs comes as much from the efficient pooling of transaction volatility risks as from the reduction in IT implementation costs. As users' transaction volatility increases, the competitive advantage of the ASP approach increases significantly. Our findings predict that the existence of ASPs would not be a temporary phenomenon. These new software deliverers are likely to compete, survive, and coexist with the traditional software vendors in the market.